Studies on association of coefficient of coancestry with progeny performance in sugarcane - Mahadevaiah, C; Hemaprabha, G; Kumar, Ravinder; Appunu, C; Sreenivasa, V; Mahadevaswamy, H.K.; Anna Durai, A; Pazhani, Adhini S (Journal of Sugarcane Research, 2021)
The utilization of superior parental lines and identification of superior families enhance the genetic gain in sugarcane. To identify the superior parental lines and superior progenies, 1889 progenies derived from twenty crosses involving genetically diverse historical parents were evaluated for juice quality and yield attributing traits.The historical parental lines were selected based on coefficient of coancestry from the tropical and subtropical parents maintained at National Hybridization Garden. Based on progeny performance, families of Co 99006 × CoSe 92423 and Co 86032 × 85R186 were found superior for number of millable canes, , Co 86032 × 85R186 and Co 8371 × CoT 8201 for cane thickness and CoSe 95422 × Co 775 and Co 8371 × CoV 92102 for sucrose content. Parental lines such as Co 86002, Co 99006 and CoLk 98184, Co 775, 85R186 and BO 130 were identified for HR Brix; Co 419 and Co 89010, CoS 510, CoV 92102 and CoSe 92423 for cane thickness; and CoLk 94184, BO 91 and BO 32 for number of millable canes. The estimates of coefficient of coancestry was negatively correlated with HR Brix and cane thickness suggesting that parental cross combination with lesser value of coefficient of coancestry or inbreeding coefficient resulted in produce the heterotic progenies. This study based on the historic parental lines selected based on the coefficient of coancestry and inference limited to only to this experimental material. The evaluation of families derived from the population parental cross combination and parental lines in replication family block design permits the estimation of BLUP based breeding values and helpful in selection of superior parental lines and superior progenies.